Peculiarities of interaction of Cu-W composite materials with thermal arc discharge plasma - Murmantsev, A.; Veklich, A.; Boretskij, V.; Kleshych, M.; Fesenko, S.; Bartlova, M. (Problems of Atomic Science and Technology, 2022)
This work is a part of acomplex investigation of the interaction of Cu-W composite materials with thermal electric arc discharge plasma. The plasma of 3.5 A DC arc discharge between novel Cu-W composite materials, fabricated by shock pressing technology at the temperature of 750°C, was studied at this stage. Spectra of such plasma emission were registered and treated to determine the radial distributions of plasma temperature in three different cross-sections of the plasma channel, namely in near-cathode, near-anode and middle cross-sections.